Atmospheric Pollution and Child Health in Late Nineteenth Century Britain - Roy E. Bailey; Timothy J. Hatton; Kris Inwood (Institute of Labor Economics (IZA), 2016)
Atmospheric pollution was an important side effect of coal-fired industrialisation in the nineteenth century. In Britain emissions of black smoke were on the order of fifty times as high as they were a century later. In this paper we examine the effects of these emissions on child development by analysing the heights on enlistment during the First World War of men born in England and Wales in the 1890s. We use the occupational structure to measure the coal intensity of the districts in which these men were observed as children in the 1901 census. We find strong negative effects of coal intensity on height, which amounts to difference of almost an inch between the most and least polluted localities. These results are robust to a variety of specification tests and they are consistent with the notion that the key channel of influence on height was via respiratory infection. The subsequent reduction of emissions from coal combustion is one factor contributing to the improvement in health (and the increase in height) during the twentieth century.
Keywords: I15; N13; Q53; 330; atmospheric pollution; health and height